2023
DOI: 10.3390/biomedicines11051429
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Spot Urinary Creatinine Concentration and Its Relationship with Body Composition Parameters in HF Patients

Abstract: Background: Low 24-h urinary excretion of creatinine in patients with heart failure (HF) is believed to reflect muscle wasting and is associated with a poor prognosis. Recently, spot urinary creatinine concentration (SUCR) has been suggested as a useful prognostic factor in selected HF cohorts. This more practical and cheaper approach has never been tested in an unselected HF population. Moreover, neither the relation between SUCR and body composition markers nor the association of SUCR with the markers of vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Only a few studies analyzed SUCR levels in patients with HF [ 15 , 16 , 17 ]. All of them have found positive association between lower SUCR and higher mortality, but only in one study, direct measurements of muscle mass [ 17 ] as a potential confounder was included in risk analysis. In this study, fat-free mass only weakly correlated with SUCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies analyzed SUCR levels in patients with HF [ 15 , 16 , 17 ]. All of them have found positive association between lower SUCR and higher mortality, but only in one study, direct measurements of muscle mass [ 17 ] as a potential confounder was included in risk analysis. In this study, fat-free mass only weakly correlated with SUCR.…”
Section: Discussionmentioning
confidence: 99%
“…However, in all aforementioned studies, direct measurements of fat-free mass were not available, making such conclusions speculative. Additionally, a recent study reported only weak correlation between fat-free mass measured by dual X-rays absorptiometry (DEXA) and SUCR levels [ 17 ]. Thus, a lot of uncertainty remains on the mechanism linking low UCER and SUCR with mortality.…”
Section: Introductionmentioning
confidence: 99%